IS FRAUD PENTAGON EFFECTIVE IN DETECTING FRAUDULENT FINANCIAL STATEMENT IN CAMBODIA? - Christian, Natalis; Kho, Jefveny; Kho, Kennily; Cahya, Cucu; Agustina, Merry (2021)
This study was conductedito examine the ability of fraudiPentagon theory to detect fraudulent financial statement. The object of this research are companies that listed in Cambodia Securities Exchange (CSX) from 2017-2020. The purposive sampling method is used to select the research sample. The study uses SPSS program to analyze data. The measurement of fraudulent financial statement is discretionary accrual. This study used arrogance, competence, pressure, opportunity and rationalization as independent variable. The result of this study show that pressure is effective detecting fraudulent financial statement. These findings will be very helpful to auditors and forensic accountant to pay more caution in aspect of pressure to detect fraudulent financial statement.